(Pyridin-2-ylmethyl)porphyrins: synthesis, characterization and C–N oxidative fusion attempts - Berthelot, Mathieu; Echaubard, Julie; Bousfiha, Asmae; Devillers, Charles H. (Comptes Rendus. Chimie)
A new route for the synthesis of meso-(pyridin-2-ylmethyl)porphyrins was developed, based on the nucleophilic attack of (pyridin-2-ylmethyl)lithium reagent on a porphyrin bearing one free meso position. The latter is then metalated with Zn(II) and Ni(II). These products were characterized by NMR spectroscopy, UV–visible absorption spectroscopy, mass spectrometry and electrochemistry. Attempts to generate the C–N-fused compound by oxidation (new bond between the nitrogen of the pyridinyl substituent and the β-pyrrolic position of the porphyrin) are also described.